Sustainable Synthesis of Nanoparticles and Composites: Green Approaches and Applications - A Review - Dr. M. Sridhar; Dr.K. Bhaskar; Dr. Boda Mahipal Reddy; Dr. Veerabathini Manohar (The Bioscan, 2025)
The sustainable synthesis of nanoparticles and composites has emerged as a key area of research due to the increasing demand for environmentally friendly and efficient methods. Traditional methods for nanoparticle synthesis often involve toxic chemicals and high energy consumption, raising concerns about sustainability. Green synthesis approaches, using plant extracts, microorganisms, and biopolymers, offer promising alternatives by providing nontoxic, cost-effective, and eco-friendly solutions. These green methods not only reduce the environmental impact but also enhance the functional properties of nanoparticles and composites. This review explores various green synthesis techniques, their applications in fields such as medicine, electronics, energy storage, and environmental remediation, and the challenges and future perspectives in advancing these approaches. Emphasis is placed on the potential of these techniques to provide sustainable solutions in nanotechnology and materials science.